Bring Back The Beat : a campaign to increase confidence among young adults to perform CPR - Choo, Charis Min Yi (2018)
This paper presents ‘Bring Back The Beat’, a digital-led communications campaign that aims to improve the confidence of young adults, aged 21 to 30, to perform cardiopulmonary resuscitation (CPR) should they witness a sudden cardiac arrest. While there has been an increase in efforts to equip Singaporeans with CPR skills, the perceived barriers and misconceptions to perform CPR remain significant. Informed by the Theory of Planned Behavior (TPB) and Bandura’s theory of self-efficacy, the campaign developed digital content strategies to increase the confidence of young adults by addressing commonly-held barriers and misconceptions that prevents them from performing CPR. To evaluate our campaign’s effectiveness, a non-equivalent control group experimental design was executed with three groups of participants (n=90). It was found that exposure to our campaign resulted in a significant improvement of our participants’ overall confidence levels (self-efficacy, emotional efficacy, and perceived behavioural control). Additionally, by coding our participants’ behaviour through a CPR simulation activity, it was found that the campaign was effective in improving the participants’ response to a cardiac arrest emergency. This is a Final Year Project by four students from Nanyang Technological University, Wee Kim Wee School of Communication and Information.